(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
In the context of the global spread of morbid obesity and the limited effectiveness of conservative therapy, laparoscopic sleeve resection of the stomach remains one of the most sought-after surgical interventions.